PEMIKIRAN USHUL FIKIH AL-GHAZÂLÎ TENTANG AL-MASLAHAH AL-MURSALAH (Studi Eksplorasi terhadap Kitab al-Mustashfâ min ‘Ilmi al-Ushûl Karya Al-Ghazâlî) - Zainal Azwar (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2015)
Abstract: Imam al-Ghazali is one of the Shafi'i’s ushul fiqh figures. As a scholar of fiqh Shafi'i fiqh, in substance, he has thought of usul fiqh which is in line with the thinking of fiqh imam, al-Shafi'i. However, in some aspects, he just has a different view, even opposite sect priest; as among about the hujjah of al-Maslahah al-mursalah as a proposition of law. So in this article, will be discussed in depth of thought usul fiqh al-Ghazali about al-Maslahah al-mursalah. The main question that will be answered in this paper is how to shape the thinking of usul fiqh al-Ghazali about al-Maslahah al-mursalah? To find the answer, the authors conducted in-depth study of the book of al-Mustashfâ min 'Ilmi al-Usul Al-Ghazali's works and other books as sources of supporting data. After reviewing critically and analytically, it can be concluded that according to Al-Ghazali, al Maslahah al mursalah can be used as proof to the requirements of the following requirements; 1. Al Maslahah it in line with the types of actions Personality '/ establishment of Islamic law. 2. Al Maslahah it should be al maslahah al Daruriyah or hajjiyah who occupies a position dharuriyah. Keyword: al-Maslahah al-Mursalah, Imam Al-Ghazali, Ushul Fiqh. Abstrak: Imam al-Ghazali adalah salah satu tokoh Syafi'i ushul fiqh. Sebagai seorang sarjana fiqh Syafi'i fiqh, secara substansi, dia telah memikirkan ushul fiqh yang sejalan dengan pemikiran imam fiqh al-Syafi'i. Namun, dalam beberapa aspek, ia hanya memiliki pandangan yang berbeda, bahkan berlawanan imam mazhab; sebagai salah tentang hujjah al-Maslahah al-mursalah sebagai dalil hukum. Jadi dalam artikel ini, akan dibahas secara mendalam pemikiran ushul fiqh al-Ghazali tentang al-Maslahah al-mursalah. Pertanyaan utama yang akan dijawab dalam makalah ini adalah bagaimana bentuk pemikiran ushul fiqh al-Ghazali tentang al-Maslahah al-mursalah? Untuk menemukan jawabannya, penulis melakukan penelitian secara mendalam tentang kitab al-Mustashfâ min 'karya Ilmi al-Ushul Al-Ghazali dan buku lainnya sebagai sumber data pendukung. Setelah meninjau secara kritis dan analitis, dapat disimpulkan bahwa menurut Al-Ghazali: 1. al Maslahah al mursalah dapat digunakan sebagai bukti untuk persyaratan persyaratan sebagai berikut. Al Maslahah itu sejalan dengan jenis tindakan syara' pembentukan hukum Islam. 2. Al Maslahah itu harus al maslahah al Daruriyyat al Hajjah yang menempati posisi dharuriyat. Kata Kunci: al-Maslahah al-Mursalah, Imam Al-Ghazali, Ushul Fiqh